2020
DOI: 10.1109/access.2020.3029859
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence in Predicting Earthquakes: State-of-the-Art and Future Challenges

Abstract: Predicting the time, location and magnitude of an earthquake is a challenging job as an earthquake does not show specific patterns resulting in inaccurate predictions. Techniques based on Artificial Intelligence (AI) are well known for their capability to find hidden patterns in data. In the case of earthquake prediction, these models also produce a promising outcome. This work systematically explores the contributions made to date in earthquake prediction using AI-based techniques. A total of 84 scientific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 92 publications
(347 reference statements)
0
18
0
3
Order By: Relevance
“…Over the last few months, many researchers have been actively contributing towards methodological development for early COVID-19 detection and screening. This has been possible due to the recent developments of artificial intelligence (AI) and machine learning (ML)-based tools and techniques which have also been applied successfully to other tasks such as anomaly detection [12][13][14], biological data mining [15,16], cyber security [17], disease detection [18][19][20], earthquake prediction [21], financial prediction [22], text analytics [23,24] and urban planning [25]. Several AI and ML driven approaches have been developed to support COVID-19 [26] through analyzing lung images acquired by means of Computed Tomography (CT) [9], CXR [11] [27], safeguarding workers in workplaces [28], identifying symptoms using fuzzy systems [29], and supporting hospitals using robots [30].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few months, many researchers have been actively contributing towards methodological development for early COVID-19 detection and screening. This has been possible due to the recent developments of artificial intelligence (AI) and machine learning (ML)-based tools and techniques which have also been applied successfully to other tasks such as anomaly detection [12][13][14], biological data mining [15,16], cyber security [17], disease detection [18][19][20], earthquake prediction [21], financial prediction [22], text analytics [23,24] and urban planning [25]. Several AI and ML driven approaches have been developed to support COVID-19 [26] through analyzing lung images acquired by means of Computed Tomography (CT) [9], CXR [11] [27], safeguarding workers in workplaces [28], identifying symptoms using fuzzy systems [29], and supporting hospitals using robots [30].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al presented an event detection approach to explore correlations among various microblogs [19]. Banna et al presented an overall review of all the machine learning techniques in predicting earthquakes [20]. Based on the background study on this topic, it has been found out that Machine Learning, Neural Network, and various other techniques are used.…”
Section: Related Workmentioning
confidence: 99%
“…Neural network (NN) based earthquake prediction systems remained center of attention from 2013 to 2017 and were followed by an era of Machine Learning (ML) and Deep Learning (DL) based methods. Al Banna et al (2020) has also approved that ML and DL have performed relatively better than the other computational approaches in making probabilistic forecasts about the expected magnitude of upcoming earthquakes in recent years.…”
Section: Introductionmentioning
confidence: 99%